Direct In vitro Regeneration of Sugarcane Var. China (Saccharum officinarum L.) Using Leaf-Sheath Explants (Plant Tissue Culture and Biotechnology, 2025)
An efficient and reproducible in vitro regeneration protocol was developed for sugarcane var. China using leaf-sheath explants. Direct multiple shoot formation without the intervention of callus from leaf-sheath was achieved on MS medium supplemented with 10.0 mg/l NAA. Ninety percent of the explants were found to induce shoots following a 90-day culture period. After 90 days of cultivation, each explant produced an average of 30.0 ± 2.50 shoots having a mean shoot length of 7.2 ± 0.50 cm on this medium. Within 30 days of being exposed to 1/2 strength of MS containing 2.50 mg/l NAA, 90% of the regenerated shoots produced roots. The average root length in this medium was 7.50 ± 2.30 cm, and there were 15.0 ± 1.25 roots produced from each shoot. Ninety percent of the in vitro raised plantlets were found to survive in the soil under a natural environment.Plant Tissue Cult. & Biotech. 34(2): 115-121, 2024 (December)